Opportunities and Barriers for Lecturers’ Career Progression: A Systematic Review of the Scientific Labour Market - Nguyen, Nu Nguyet Anh; Nguyen, Ninh (Italian Sociological Review, 2025)
Scientific labour market mobility is important for stability in tertiary education worldwide. The systematic research evaluates academic career progression challenges and trends through analysis of 792 Web of Science and Scopus papers spanning from 1990 to 2025. A bibliometric study identified research trends and nodes. and Scopus papers spanning from 1990 to 2025. Gender equality problems combine with limited funding alongside restrictive institutional barriers to create barriers for women in educational development. Limited professional development, international cooperation, and adoption of educational technology remain major challenges. Conversely, growth opportunities include enhanced leadership training, interdisciplinary collaboration, and digital transformation, all of which foster innovation and equity. This study reinforces equality, employability, and leadership as the main elements shaping academic career mobility. More importantly, this study suggests future paths of research that include the support of multicultural and multidisciplinary scholarships, and the expansion of engagement in higher education. The bibliometric analysis revealed a growing trend in research in providing equity for academic opportunities to minority ethnic and socioeconomic background groups.